Glucocorticoids Suppress T Cell Function by Up‐Regulating MicroRNA‐98. Issue 7 (2nd July 2013) - Davis, Trevor E.; Kis‐Toth, Katalin; Szanto, Attila; Tsokos, George C.
<x xml:space="preserve">Abstract</x> Objective To identify microRNAs (miRNAs) in human T cells that can explain known antiinflammatory properties of steroids. Methods Activated human CD4+ T cells from healthy donors were exposed to 1 μM methylprednisolone (MP) in vitro and then subjected to miRNA and messenger RNA microarray analyses. Changes in expression profiles were recorded. Using quantitative polymerase chain reaction (qPCR), flow cytometry, and enzyme‐linked immunosorbent assay (ELISA), we confirmed the suppression of predicted targets, and through miRNA transfection experiments, we could suggest mechanistic links. Results We identified numerous steroid‐responsive genes and miRNAs—many known and some novel—including multiple previously unknown proinflammatory genes suppressed by MP. Further studies using qPCR, flow cytometry, and ELISA demonstrated that methylprednisolone increased the expression of miRNA‐98 (miR‐98) and suppressed the levels of predicted targets, including interleukin‐13 and 3 tumor necrosis factor receptors (TNFRs): Fas, FasL, and TNFR superfamily member 1B. Forced expression of miR‐98 in T cells resulted in suppression of the same targets. Conclusion The findings of this study demonstrate a link between miR‐98 expression and the effects of MP and provide evidence suggesting that MP acts through miR‐98 to inhibit specific proinflammatory targets. Identification of this antiinflammatory mechanism of glucocorticoids is important, since it may pave the way toward the elusive goal of dissociating adverse effects from therapeutic effects.